Substance use to enhance occupational performance and experience: a critical interpretive synthesis/Uso de substâncias para melhorar o desempenho e a experiência ocupacional: uma síntese interpretiva crítica - Kiepek, Niki; Beagan, Brenda; Phelan, Shanon (Cadernos Brasileiros de Terapia Ocupacional, 2019)
Introduction: Substance use, as an occupation, is typically portrayed as problematic and the target of occupational therapy intervention and remediation. At the same time, psychoactive substances may be used to enhance mood, cognition, occupational performance, and/or experience, a perspective that is largely absent from occupation scholarship. Objective: We examine substance use in relation to the enhancement of occupation, drawing on the theoretical notion of agential realism. This theory suggests that in the social world ‘reality’ is not so much objective fact, stable and predictable, but rather continuously produced and reproduced, through doing and intra-active becoming. Method: A selected integrative, critical interpretive synthesis of the literature was conducted. The analysis is focused on synthesizing literature about substance use and enhancement of occupation. Results: Occupation does not exist independent of the doing, but also in ‘becoming’. Sometimes using a substance is in itself an occupation – having a drink, or going out for coffee. Sometimes using a substance is a means to enhance another occupation – taking erectile dysfunction medication to improve sex, or amphetamines to improve studying. Sometimes using a substance simply alters the experience of an occupation – using cannabis or psychedelics to enhance the experience of listening to music. Conclusion: Adopting a focus on occupation may encourage novel ways of understanding substance use and what constitutes optimal quality of life and meaningful experiences. It may also facilitate better understandings of how people employ alternative, non-substance means to achieve desired occupational outcomes.